La Sardegna nel Settecento - Carta, Luciano (Sardiniae memoria, 2023)
The text is a guided itinerary in the knowledge and interpretations now critically acquired, but also in those in need of further investigation, dedicated to the Sardinian eighteenth century, one of the most significant centuries of the confrontation between tradition and innovation, between preservation and reformism, that Sardinian history can number. This is the first volume in the "Sardiniae memoria" series, a series of textbooks on Sardinia, designed to be usable by both university students and high school seniors.